Referendum study 1957 - Särlvik, Bo; Westerståhl, Jörgen (University of Gothenburg, 1987)
Since 1956 a election study have been carried out in conjunction with every parliamentary election in Sweden. Likewise studies have been carried out in conjunction with the two referenda that have taken place since then. In 1957 a referendum on the general supplementary pension scheme (ATP) took place. The respondents were questioned three times, two interviews were held before the day of the referendum and a mail survey were sent to them after the referendum. The study contains questions on the general supplementary pension scheme, national basic pension, opinion of the three proposals, sources of information, and newspaper reading. Apart from the questions concerning the referendum, the study examines Swedish national defence by including questions about the war risk and the atomic bomb.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

Since 1956 a election study have been carried out in conjunction with every parliamentary election in Sweden. Likewise studies have been carried out in conjunction with the two referenda that have taken place since then. In 1957 a referendum on the general supplementary pension scheme (ATP) took place. The respondents were questioned three times, two interviews were held before the day of the referendum and a mail survey were sent to them after the referendum. The study contains questions on the general supplementary pension scheme, national basic pension, opinion of the three proposals, sources of information, and newspaper reading. Apart from the questions concerning the referendum, the study examines Swedish national defense by including questions about the war risk and the atomic bomb.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Folkomröstningsundersökningen 1957
FU57
Keywords: internal politics; inrikespolitik; Retirement; Pension; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap